Palliative Care: A Holistic Discipline. (March 2016) - Greer, Steven; Joseph, Marie
Although mind and body are inextricably interwoven, psychological factors have received insufficient attention within medicine. The biomedical model though necessary is not sufficient. In medicine and particularly in palliative care, a holistic biopsychosocial approach is required. A number of examples from clinical practice in a hospice setting are presented.